Antimicrobial and Antioxidant Effect of selected Essential Oils in Refrigerated Beef Burger - Ayyad, Ziad; Qurie, Mohannad; Zamel, Salah; Mudalal, Samer; Al- Rimawi, Fuad (Journal of Neonatal Surgery, 2025)
Microbial growth and oxidation are considered to be the major causes of beef burger deterioration.Synthetic antimicrobial and antioxidants are therfore used to prevent or delay microbial growth and oxidation process. Unfortunately, these substances are not safe and may cause harmful impacts on human health, which arose the need to search for natural alternatives in the food industry. In this study, essential oils of clove, thyme, and rosemary serve as natural preservatives to increase the shelf life of refrigerated beef burger up to 7 days without using synthetic antimicrobial and antioxidant agents. Essential oils were added to beef burger at two different concentrations (1 and 1.5% v/w). In addition, two positive control samples for antimicrobial and antioxidant agent were treated with 2% potassium lactate (PL) and 100 ppm Butylated hydroxytoluene (BHT) respectively. All samples were kept at 4°C for 7 days (study period). Measurement of the antimicrobial activity of essential oils was performed by testing total plate count, total coliforms, and Staphylococcus aureus. The oxidation stability test was carried out by thiobarbituric acid reactive substances (TBARS) test, and expressed as mg of malonaldehyde/ kg beef burger, in addition to that, the pH of each sample was examined. Essential oils added to beef burger showed strong antimicrobial effects against the examined microbes. The obtained results revealed that, clove essential oil (CEO) added at concentration 1.5% reduced the microbial activity of Staphylococcus aureus by 54% compared with negative control sample, also, there is a significant difference between it and all treated samples. In addition, results indicated that CEO at both concentrations 1% and 1.5% had the most effect on reducing microbial growth of total coliform (TC) compared with other stored samples. Total plate count results showed that essential oils at all different concentrations used in this study led to reduction in microbial growth in the burger samples without any significant differences between these essential oils (EOs). Regardingthe chemical indicators, CEO at concentrations of 1% and 1.5% were the most effective and retard oxidation by 24% and 35%, respectively compared with negative control sample. Moreover, Thyme essential oil (TEO) at a concentration of 1% and 1.5%, reduced the percentage of oxidation by 14% and 31%, respectively compared with the negative control sample.